Operational Risk, Translation, and Globalization - Barbara Czarniawska (Contemporary Economics, 2012)
This paper compares a translation of a global (more specifically, European) regulation into two local contexts, setting this process in a broader context of the all-pervading risk management. The two countries are Sweden and Poland, both relatively untouched by the current financial crisis, and the regulation is Basel II Accord. In both countries, the translation is shaped by the past history, and the present circumstances. The results show that, in spite of local differences, there is a common belief in quantification of risks as the main remedy and therefore the main way of managing them. Abstract and vague formulations, combined with sophisticated calculation techniques, win over the complications of actual practices. The role of researchers in this process is also examined. A study illustrates also the advantages of translation theory versus diffusion theory of spreading of ideas.
Keywords: M48; 330; translation; diffusion; globalization; operational risk; risk management